Monitoring and Controlling of Mobile Harvesting Robot Through Wireless LAN - Lim, Yu Jian (2004)
This research project presents a modification of a mobile harvesting robot for communication of human operator with the machine through wireless LAN networking. The adopted harvesting strategy relies on an operator to guide the vehicle through viewing real time video of the workspace to locate the fruit, while the robotic system plans the cutting sequence and makes the approximation for detaching of the fruit. This new strategy will reduce the overall cutting cycle by avoiding the time taken for detection and location of the fruit. A software program was developed using Visual Basic for the operator to monitor and control the mobile harvesting movement remotely. Java Applet has been integrated into this software to continuously transmit the images from the CMOS web camera to the human operator in real time. The operator communicates with the robot server through a pair of radio Ethernet devices. The location of fruit and position of the mobile robotic can be easily retrieved and sent over the wireless TCPIIP protocol. This research has defined the X-axis as the horizontal axis of the target, Y-axis as the distance of target from the mobile harvester and the Z-axis as the vertical axis of the target. All the X, Y and Z - axis coordinates of the targeted h i t can be determined by the triangulation computation method using the video base positioning technique. To move the mobile harvesting robot to the X, Y and Z coordinates of the target, modification has been done including the attachment of few sensors to the mobile harvesting robot. The input signal to the robot controller commands it to move and stop the robot at the X, Y and Z coordinates precisely.